Artificial controlled model of blood circulation system for adhesive evaluation. Issue 1 (December 2017) - Jung, Sang-Myung; Chung, Goo; Shin, Hwa
Abstract Since there are several casualties due to uncontrolled bleeding resulting from simple injury to surgery, effective styptic or vessel adhesives are important; however, their development is limited by the lack of standardized systems to evaluate potential compounds. The current study outlines the development of an aorta styptic evaluation system, comprising of decellularized swine aorta tissue and a heart pump-mimicking system. Although the cells in the swine aorta were removed, the structural stability of the aorta was sustained due to the maintenance of the extracellular matrix. Using a control adhesive, Cyanoacrylate, the developed model was found to have similar adhesive efficacy to intact aorta. The circulatory-mimicking system was designed to mimic the beat rate and strength of blood-flow from the heart, which was necessary to evaluate the adherent efficacy. The decellularized aorta improves instabilities of intact tissues, which occurs on account of storage and origin, thereby allowing for a more standardized system. The system was able to simulate several symptoms of circulation, according to patient age and health, by adjusting pumping frequency and intensity. Therefore, this system can be used as a standardized evaluation system for screening adhesives. Further, it would also evaluate other medical devices, such as stent or medications.